Pengaruh Model Project Based Learning Terhadap Hasil Belajar Kognitif dan Sikap Peduli Lingkungan - Mar'i Naufal Rafsanzani; Arwin Surbakti; Darlen Sikumbang (Universitas Lampung, 2020)
This study aims to determine the effect of the projectbased learning model in improving cognitive learning outcomes and students' environmental care student attitudes. Research method way quasi-experimental with a pretest posttest non-equivalent control group design. The research sample technique was random sampling technique. The results showed the use of project based learning models can improve cognitive learning outcomes of students with an average N-gain experimental group higher (0.33) than the control group (0.21) with the implementation of learning activities of the experimental group that way very good (90, 62%). In addition, the use of project based learning models can also significantly increase the student attitude of environmental care with an average experimental group that way higher (76.13) than the control group (69.30) so that the experimental group is in good criteria while the control group gets sufficient criteria.Penelitian ini bertujuan untuk menentukan pengaruh model project based learning dalam meningkatkan hasil belajar kognitif dan sikap peduli lingkungan peserta didik. Metode penelitian quasi experiment dengan rancangan pretest postest non equivalent control group design. Sampel penelitian kelas VII 1 dan VII 2 SMP Negeri 2 Pesawaran. Pengambilan sampel penelitian menggunakan teknik random sampling. Hasil penelitian menunjukkan penggunaan model project based learning dapat meningkatkan hasil belajar kognitif peserta didik dengan rata-rata N-gain kelompok eksperimen lebih tinggi (0,33) dibanding kelompok kontrol (0,21). Selain itu, pengunaan model project based learningjuga dapat meningkatkan sikap peduli lingkungan secara signifikan dengan rata-rata kelompok eksperimen lebih tinggi (76,13) dibanding kelompok kontrol (69,30) sehingga kelompok eksperimen mendapatkan kriteria baik sedangkan kelompok kontrol mendapatkan kriteria cukup.Kata kunci: hasil belajar kognitif, project based learning, sikap peduli lingkungan